Ordenamento sanitário, profissões de saúde e cursos de partos no século XIX - Carneiro, Marinha (História: revista da Faculdade de Letras da Universidade do Porto, 2018)
Being part of a wider research, the present article approaches the sanitary management notion arisen from the new medical paradigm which emerged in the 19th century and its effects on the various health professions, focusing in more detail on the promotion of midwifery courses at medical schools which have introduced a new training model for midwifes.